Physiological traits in relation to yield improvement in chickpea (Cicer arietinum L.) under depleting soil moisture environment - Summy, Summy; Boora, K.S.; Sharma, K.D. (The Indian Journal of Genetics and Plant Breeding, 2016)
The chickpea genotypes along with F4 progeny lines differing in their behavior towards drought were evaluated for seed yield, yield attributes and physiological traits. Drought decreased the leaf water potential, leaf osmotic potential and relative water content in both parents and progeny lines. The parent RSG 931 had more plant water status as compared to HC 1 under drought condition. The progeny lines G11, G10, G 04 and G 05 showed the similar results. Leaf water potential, osmotic potential and RWC had a significant association with seed yield (r = 0.86, 0.95 and 0.92, respectively). The seed yield decreased in drought stress condition but decrease in yield of RSG 931 (19.27%) was less than HC 1 (37.32%). The parent RSG 931 and the progeny lines G11, G10, G 04 and G 05 had better plant water status, CTD and photochemical efficiency and these traits were directly associated with seed yield.